New Investigation for the Liu-Story Scaled Conjugate Gradient Method for Nonlinear Optimization - Eman T. Hamed; Rana Z. Al-Kawaz; Abbas Y. Al-Bayati (Journal of Mathematics)
This article considers modified formulas for the standard conjugate gradient (CG) technique that is planned by Li and Fukushima. A new scalar parameter θkNew for this CG technique of unconstrained optimization is planned. The descent condition and global convergent property are established below using strong Wolfe conditions. Our numerical experiments show that the new proposed algorithms are more stable and economic as compared to some well-known standard CG methods.